Magnitude of Neglected Tropical Diseases in Indonesia at Postmillennium Development Goals Era - Tri Wibawa; Tri Baskoro Tunggul Satoto (Journal of Tropical Medicine)
The world will enter the postmillennium development goals 2015 era. The achievements of the millennium development goals (MDGs) as a global development target need to be evaluated. A sustainable new reasonable target is important for neglected tropical diseases (NTD) elimination in Indonesia. This review describes the NTD situation in Indonesia and highlights problems beneath the NTD transmission. Multidisciplinary approach is a promising strategy to help the marginalized people.